201k views
4 votes
Given the equation 4x + 7 = 3(2x − 5), solve for the variable. Explain each step and justify your process. B. Sam solved a similar equation below. Is Sam's solution correct? Explain why or why not.

1 Answer

5 votes
Equation: 4x + 7 = 3(2x - 5)

Step-by-step solution:

• Expand brackets

-> 4x + 7 = 6x - 15

• Move x variable to a side and the numbers to another

-> 4x - 6x = -15 - 7

• Solve

-> -2x = -22

• Multiply both sides by (-1)

-> -(-2x) = -(-22)
-> 2x = 22

• Divide both sides by 2

-> x = 22/2

-> x = 11

• Justification
-> Put x = 11 in original equation
-> 4(11) + 7 = 3( 2(11) - 5)
-> 44 + 7 = 3(22 - 5)
-> 51 = 3(17)
-> 51 = 51
-> 51 - 51 = 0
-> 0 = 0
Since both sides are equal to each other, the answer to the equation is correct.

I don't know Sam's equation so I'm not gonna answer that.
User Om Deshmane
by
6.0k points